STRATEGI PERCEPATAN PEMENUHAN LISTRIK DI DAERAH DALAM RANGKA PEMERATAAN EKONOMI DAN PENINGKATAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN TANJUNG JABUNG TIMUR - Dessy Fitrian (Bajang Institute, 2026)
The unequal distribution of electricity infrastructure remains one of the major challenges in achieving equitable regional development and improving community welfare, particularly in geographically isolated and coastal areas. Although the electrification ratio in Tanjung Jabung Timur Regency has increased significantly, several remote hamlets remain without access to the national electricity grid due to inadequate transportation infrastructure, difficult geographical conditions, high investment costs, and limited economic feasibility. This study aims to formulate strategies to accelerate electricity provision in underserved areas as an effort to support regional economic equity and enhance community welfare. The research employed a qualitative descriptive approach using secondary data collected from government planning documents, statistical reports, electricity development programs, relevant regulations, and scientific literature. Data were analyzed through descriptive and policy analysis to identify the main constraints and formulate strategic recommendations. The findings reveal that the primary barriers to rural electrification include poor road connectivity, damaged bridges, dispersed settlements, high capital and operational costs, and the limited financial viability of grid expansion. To overcome these challenges, an integrated strategy is required through strengthening coordination between local governments, PT PLN (Persero), and the Ministry of Energy and Mineral Resources, improving supporting transportation infrastructure, expanding the Village Electrification Program, optimizing substations and transmission networks, and utilizing renewable energy-based off-grid systems for isolated communities. These strategies are expected to accelerate universal electricity access, reduce regional development disparities, stimulate local economic activities, and improve the quality of life of communities in remote areas